Experimental characterization of stone masonry in shear and compression - Vasconcelos, Graça (2009)
Shear and compressive mechanical properties are needed for the evaluation of the strength of masonry shear walls by means of simplified methods or numerical analysis. This, in turn, allows to design or assess masonry buildings subjected to combined vertical and horizontal loading. Even if many results on the mechanical properties of modern brick and block masonry are available in the literature, only a few results exist for stone masonry.Here, the shear and compressive strength parameters of stone masonry using granite blocks are provided. In addition, a first aspect addressed is the shape of the shear stress-displacement diagrams under monotonic and cyclic loading. A second aspect addressed is the influence of the surface roughness and of the bed joint material on the compressive behavior of masonry. (C) 2009 Elsevier Ltd. All rights reserved.